Pelaksanaan Pertunangan di Gampong Cot Seutui Kecamatan Kuta Makmur Kabupaten Aceh Utara: (Analisis Terhadap Qanun Aceh Nomor 6 Tahun 2014 Bagian Keempat Tentang Ikhtilath) - Andika, Muhammad; Mahmudi; Abdullah; Hafidhillah, Haikal (Yayasan Madinah Al-Aziziyah, 2023)
This study focuses on changes in traditional customs in Gampong Cot Seutui, Kuta Makmur District, North Aceh Regency, particularly regarding engagement practices and violations of Islamic law and Aceh Qanun Number 6 of 2014 on Ikhtilath. The research aims to describe the engagement traditions and how the community perceives shifts that could potentially lead to free interaction between men and women (ikhtilath). Using a qualitative approach with normative and phenomenological methods, data was gathered through observation, interviews, and documentation. The findings reveal that engagement events are often conducted lavishly, resembling wedding ceremonies, with photo spots and ring exchange sessions. The groom-to-be places a ring on the bride-to-be’s finger, followed by photo sessions displaying the ring, giving the impression of a formalized relationship. These practices are considered to violate Islamic principles and the Qanun, as they allow for free interaction between men and women outside permissible limits. The study highlights the influence of external cultures on local traditions, emphasizing the need to preserve Islamic values in every aspect of customary practices.